Soybean growth-promotion and Heterodera glycines suppression in two application methods of Bacillus strains - Dalvan do Nascimento, Daniel [UNESP]; Rodrigues, Mariana [UNESP]; Junior Ferreira, Rivanildo [UNESP]; Marchioro, Vinícius [UNESP]; Macedo da Silva, Edicleide [UNESP]; Alberto Silva Junior, Carlos [UNESP]; Cristina Kupper, Katia; Antonio Polanczyk, Ricardo [UNESP]; Luiz Martins Soares, Pedro [UNESP] (Elsevier, 2022)
The soybean cyst nematode (SCN), Heterodera glycines Ichinohe, is a pest that is difficult to control worldwide and causes severe damage to soybeans. The demand for sustainable control strategies with Bacillus has increased; however, the use of Bacillus for SCN control is poorly studied compared to that of its use against other pests. We tested 19 isolates from three Bacillus spp. (B. subtilis, B. amyloliquefaciens, and B. methylotrophicus), which were assessed through inoculation in-furrow and via seed treatment (ST) to evaluate soybean growth promotion and SCN suppression. The effects of the Bacillus strains were compared with commercial biological and chemical agents (B. subtilis UFPEDA 764, abamectin, and cadusafos) and controls (with and without SCN infection). Plant height, fresh and dry shoot weight, pod number, chlorophyll index, total egg and second juvenile stage of SCN (J2s), J2s densities, and SCN reproductive factors were evaluated 70 days after sowing. Multivariate data were subjected to principal component analysis (PCA), which identified the optimal treatments for plant growth promotion and SCN suppression by suggesting correlations between them. The Bacillus treatments were not able to reduce initial nematode concentrations at reproductive factor levels <1.0; however, all treatments with Bacillus spp. reduced the final average nematode density by 76.72 % in ST and 66.15 % in-furrow compared to the untreated control (P < 0.01). The number of cysts in the soil was reduced by an of average 56.6 % in the ST and 35.33 % in-furrow. While in-furrow inoculation increased soybean germination, ST promoted greater plant growth. Bacillus amyloliquefaciens ACB-08 (4) and ACB-23 (30) were the most effective in promoting soybean growth and suppressing SCN.
Keywords: Bacillus inoculation; In-furrow; Nematode control; Plant growth-promoter; Seed treatment; Soybean cyst nematode